P101 Surface parasternal intercostal electromyogram (sEMGpara) as a monitoring tool in cystic fibrosis. (16th November 2010) - Reilly, C; Jolley, C; Elston, C; Rafferty, G F; Moxham, J
Abstract : Lung function has been traditionally accepted as the primary monitoring tool in cystic fibrosis. The rate of change in lung function however, is slowing and is now as low as 1% per annum. Alternative monitoring tools to assess disease severity are therefore required. Measuring neural respiratory drive (NRD) using diaphragm electromyography (EMG) provides a sensitive measure of load on the respiratory system. The invasive nature of this technique limits is application, however measurement of NRD by sEMGpara is non-invasive and has potential clinical application in monitoring respiratory function in cystic fibrosis (CF). Hypothesis: That NRD measured by sEMGpara%max can be used to assess the change of ventilatory mechanics during an infective exacerbation in CF. Methods: Eight patients [median (range) 20 (20–25) years old, three females] with CF, admitted to hospital with an acute chest infection were studied. The studies were performed within 48 h of admission and on the day of discharge. At both time points spirometry and sEMGpara were measured. sEMGpara was recorded from bipolar surface electrodes placed 3 cm bilaterally from the midpoint of the sternum in the second intercostal spaces (positive electrode on the right side of the chest). The reference electrode was placed on the lateral aspect of the clavicle. For EMG analysis the root mean square (RMS) was calculated and peak RMS of the resting EMG was expressed as a percentage of peak RMS of the maximum (EMG %max) obtained during inspiratory capacity manoeuvres. Results: The median (range) length of stay was 10 (5–22) days. There was a significant reduction in median (range) sEMGpara%max between the first measurement and discharge [19.5 (8–28)% vs 13.5(6–18)% p=0.008]. The reduction in sEMGpara%max was coupled with an improvement in FEV1 % predicted [41 (20–62)% vs 46 (34–85)% p=0.02] and VC% predicted [70 (38–79)% vs 74 (45–90)% p=0.033] on discharge. Conclusion: These findings support the hypothesis that NRD measured by sEMGpara%max has potential as a clinical tool to assess changes in ventilatory function in patients with CF following an acute exacerbation.